Empresa júnior: espaço para construção de competências - Marques, Rafaela de Almeida Campos (2012)
In recent years, the concept of competence has gained preeminence in both, the academic and organizational environment. As a result of the significant changes that occurred in the market throughout the 1980s, the stable and predictable environment became increasingly turbulent, unpredictable and complex. This complex new scenario required a new set of skills from the business professional to enable them to deal successfully with new challenges. Within the higher education institutions, students began to feel the necessity to establish contact with the professional market and acquire a deeper knowledge and level of skill than those obtained in the classroom. In 1988, as a result of this dynamic, a French concept which was developed in the mid-1970s, was brought to Brazil, the concept of Junior Enterprise - JE. JE is an association entirely constituted and managed by graduating students. The students in this program, provide consulting services to companies under the guidance of their experienced professors. Due to the expressive growth in the number of JEs in the country, concerns have emerged about the compatability of this phenomenon with the reality of Brazil s higher education institutions. The present study aims to identify and analyze what skills were developed by graduating students in the Junior Enterprise program in the Business Administration Course at Uberlândia s Federal University, Apoio Consultoria from 1994 (the date which the association was founded) to 2010. The study also seeks to verify if the skills learned in the JE contributed to their professional career development. The methodology employed in the research was the qualitative method. The data collection techniques applied were direct observation, document analysis and episodic interview with former members of Junior Enterprise. Therefore, adopting the theoretical-conceptual parameters of analysis proposed by Paiva & Melo (2008), six competencies dimensions were identified: key-competences (meta-competencies and trans-competencies), cognitive, functional, behavioral, ethical and political competencies. The most cited competence among the interviewees was the behavioral competence. The study found a prevalence of positive conceptions about the learning environment of the Junior Enterprise (Apoio Consultoria) and it\'s positive contributions on the professional career development of those surveyed.